If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + -6 = qr Reorder the terms: -6 + 5n = qr Solving -6 + 5n = qr Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 5n = 6 + qr Combine like terms: -6 + 6 = 0 0 + 5n = 6 + qr 5n = 6 + qr Divide each side by '5'. n = 1.2 + 0.2qr Simplifying n = 1.2 + 0.2qr
| 7p^2-17p-12=0 | | 7-(5t-13)=-25 | | -2.5+x=-7.4 | | 2x^3+5=24 | | 5=-3x+20 | | 8.2xn=31.98 | | 121=12x-x | | -x-7+2x=19 | | 5x=-3x+20 | | Tan(3x+13)=cot(2x+23) | | 8x-17=4x+4 | | 4*7/3*-6/-5 | | 18x/6-12 | | .25x=x+12 | | 4w+6=-22 | | 8q+6=4q-14 | | 14y-9y-7=77.20 | | -0.05s^2-1.1s+200=0 | | 17a=4 | | 6x+6(2)=18 | | 12x-x=121 | | 200=0.05s^2+1.1s | | 0=n-15 | | 4+6x+110=180 | | 7(x-6)-5=-47 | | 10x+100=180 | | t=5s+20.14 | | 5x-17=-13 | | 6y=-32 | | 20x+120=180 | | -13=5x-17 | | 3y-9=7x |